AKUNTANSI NILAI WAJAR, VOLATILITAS LABA, DAN PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN - Zahro, Mar’atus (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research aims to obtain empirical evidence whether the application of fair value accounting effect on earnings volatility and the effect of the application of fair value accounting to the manipulation behavior of financial statements through earnings management practices. This research also aims to investigate the effect of earnings volatility to earnings management in public bank companies listed in Indonesian Stock Exchange. The samples of this research is all of public bank companies existed in Indonesia in the year of 2010-2011 which were listed in Indonesian Stock Exchange. The research data were collected from bankâs quarterly financial statement for the period of 2010 until 2011. Purposive sampling method was used to determine research sample. From this method, this research collected 80 observations from 10 public bank companies for 2 years. The results showed that fair value accounting has no effect on earnings volatility. This research also not found an empirical evidence that fair value accounting effects the behavior of manipulating earnings through earnings management practices. This research obtain an empirical evidence that earnings volatility has a positive effect on earnings management. Management will likely choose to keep the value of earnings is stable compared to the value of earnings tend to be volatile.Keyword: Fair value accounting, earnings volatility, earnings management